Expression of programmed death‐1 in sentinel lymph nodes of breast cancer. Issue 6 (28th November 2017) - Tatara, Takashi; Mukohara, Toru; Shimono, Yohei; Yamasaki, Takashi; Imamura, Yoshinori; Funakoshi, Yohei; Toyoda, Masanori; Kiyota, Naomi; Takao, Shintaro; Kono, Seishi; Kakeji, Yoshihiro; Minami, Hironobu
Abstract : Background and Objectives: To explore whether lymphocytes in sentinel lymph nodes (SLNs) are highly exposed to tumor neoantigens and thus express high level of programmed death 1 (PD‐1), we examined PD‐1 expression in SLNs and non‐sentinel regional lymph nodes (non‐SLNs) in breast cancer. Methods: We performed PD‐1 immunohistochemistry in two cohorts: 40 metastasis‐negative SLNs including 10 patients for each subtype (luminal A‐like, luminal B‐like, HER2, and triple negative breast cancer [TNBC]); and 25 pairs of metastasis‐positive SLNs and non‐SLNs (10 luminal A‐like, 10 luminal B‐like, and 5 TNBC). Results: Among 40 metastasis‐negative SLNs, 34 and 6 samples were PD‐1 intensity grade 1 (low) and 2 (high), respectively. PD‐1 intensity correlated with PD‐1‐positive lymphocyte numbers ( P = 0.005); TNBC had the highest PD‐1 lymphocyte numbers among all subtypes. The median PD‐1‐positive lymphocyte number was higher in SLNs than non‐SLNs. In most cases, more lymphocytes in SLNs expressed PD‐1 than those in non‐SLNs ( P < 0.0001). Conclusions: TNBC had the greatest PD‐1 expression among all subtypes, and metastasis‐positive SLNs had more PD‐1‐positive lymphocytes than downstream non‐SLNs. These data suggested that lymphocytes in SLNs are activated following exposure to tumor neoantigens and thus tumor specific, and could be utilized as a biomarker platform.